A family‐based association analysis and meta‐analysis of the reading disabilities candidate gene DYX1C11. Issue 2 (22nd January 2013) - Tran, C.; Gagnon, F.; Wigg, K.G.; Feng, Y.; Gomez, L.; Cate‐Carter, T.D.; Kerr, E.N.; Field, L.L.; Kaplan, B.J.; Lovett, M.W.; Barr, C.L.
Abstract Reading disabilities (RD) have a significant genetic basis and have shown linkage to multiple regions including chromosome 15q. Dyslexia susceptibility 1 candidate gene 1 (DYX1C1) on chromosome 15q21 was originally proposed as a candidate gene with two potentially functional polymorphisms at the −3G/A and 1249G/T positions showing association with RD. However, subsequent studies have yielded mixed results. We performed a literature review and meta‐analysis of the −3G/A and 1249G/T polymorphisms, including new unpublished data from two family‐based samples. Ten markers in DYX1C1 were genotyped in the two independently ascertained samples. Single marker and −3G/A:1249G/T haplotype analyses were performed for RD in both samples, and quantitative trait analyses using standardized reading‐related measures was performed in one of the samples. For the meta‐analysis, we used a random‐effects model to summarize studies that tested for association between −3G/A or 1249G/T and RD. No significant association was found between the DYX1C1 SNPs and RD or any of the reading‐related measures tested after correction for the number of tests performed. The previously reported risk haplotype (−3A:1249T) was not biased in transmission. A total of 9 and 10 study samples were included in the meta‐analysis of the −3G/A and 1249G/T polymorphisms, respectively. Neither polymorphism reached statistical significance, but the heterogeneity for the 1249G/T polymorphism was high. The results of this study do not provide evidence for association between the putatively functional SNPs −3G/A and 1249G/T and RD. © 2013 Wiley Periodicals, Inc.